ESTIMASI PARAMETER REGRESI LOGISTIK DATA PANEL EFEK TETAP UNTUK T=2 - Umi Yuliatin; Dedi Rosadi; Ezhari Asfa’ani (Math Educa Journal, 2022)
Logistic regression is a dichotomous classification method that uses several mathematical concepts in the estimating of variables parameters. In the estimation of parameter using the MLE (Maximum Likelihood Estimation) estimation method are obtained by Newton Raphson's numerical method. Unfortunately, this estimation doesn’t work in binary panel data with fixed effects for time T=2 because the present of fixed effec .  Thus, Conditional MLE is used to provide consistent estimator of . This estimation shows by sample data  N=1.151 obtained  while the discussion shows the parameter values are at .